Análise de argamassas com substituição parcial do cimento Portland por cinza residual de lenha de algaroba - Melo, Fellipe César Andrade Costa (2012)
With the increase in cement consumption, it has quickly become one of the inputs most consumed by mankind over the last century. This has caused an increase in CO2 emissions, as cement production releases large quantities of this gas into the atmosphere. Adding this fact to the growing consciousness of environmental preservation, it has led to a search for alternatives to cement to complement its derivatives, in the form of waste materials like the ashes. This research aimed to analyze the properties of mortars in fresh and hardened state with partial replacement of Portland cement by residual algaroba wood ash (CRLA) potteries produced by the state of Rio Grande do Norte. The CRLA was collected and sieved, where part of it was ground and characterized in comparison with that just sifted, being characterized according to its chemical composition, grain size, fineness, density, bulk density and index of pozzolanic activity. It was found that the wood ash does not act as pozzolan, and grinding it has not changed its characteristics compared to those just sifted, not justifying its use. Two traces were adopted for this research: 1:3 (cement: fine sand) and 1:2:8 (cement: hydrated lime: medium sand); both in volume, using as materials the CRLA just sifted, CP II F-32 Portland cement, CH-I hydrated lime, river sand and water from the local utility. For each trace were adopted six percentages of partial replacement of cement for wood ash: 0% (control) 5%, 7%, 10%, 12% and 15%. In the fresh state, the mortars were tested towards their consistency index and mass density. In the hardened state, they were tested towards their tensile strength in bending, compressive strength and tensile adhesion strength, and its mass density in the hardened state. The mortar was also analyzed by scanning electron microscopy and X-ray diffraction. Furthermore, it was classified according to NBR 13281 (2005). The results showed that up to a content of 5% substitution and for both traces, the residual algaroba wood ash can replace Portland cement without compromising the mortars microstructure and its fresh and hardened state